Changing cultural tastes : writers and the popular in modern Germany - Waine, Anthony Edward, 1946- (Berghahn Books, 2007)
"Changing Cultural Tastes offers a critical survey of the taste wars fought over the past two centuries between the intellectual establishment and the common people in Germany. It charts the uneasy relationship of high and popular culture in Germany in the modern era. The impact of National Socialism and the strong influence from Great Britain and the United States are assessed in this cultural history of a changing nation and society. The period from 1920 to 1980 is given special prominence, and the work of significant writers and artists such as Josef von Sternberg and Bertolt Brecht, Elfriede Jelinek and Rolf Dieter Brinkmann, Erwin Piscator and Heinrich Boll, is closely analysed. Their work has reflected changing tastes and, crucially, helped to make taste more pluralistic and democratic."--Jacket